Effectiveness and safety of a new clip for delivery using a duodenoscope for bleeding after endoscopic sphincterotomy - Yamaguchi, Atsushi; Kamada, Hiroki; Semba, Shigeaki; Kato, Naohiro; Okuda, Yasuhiro; Teraoka, Yuji; Mizumoto, Takeshi; Tamaru, Yuzuru; Hatakeyama, Tsuyoshi; Kouno, Hirotaka; Yoshida, Shigeto (Endoscopy International Open, 2024)
Background and study aims Hemostasis for post-endoscopic sphincterotomy (post-EST) bleeding involves no standard strategy. New clips designed for delivery using the duodenoscope (SureClip, Micro-Tech, Nanjing, China) have been utilized for gastrointestinal bleeding hemostasis and bleeding prevention after polypectomy and papillectomy. We retrospectively analyzed the effectiveness and safety of SureClip for post-EST bleeding.Patients and methods Of 608 patients with endoscopic sphincterotomy (EST), 41 cases (6.7%) experienced post-EST bleeding from 2019 to 2023. Of these patients, 24 underwent hemostasis by SureClip, and the success rate of complete hemostasis and complication by hemostasis by SureClip was analyzed.Results In 12 and 12 patients with urgent and delayed bleeding, 11 (91.7%) and 11 (91.7%) had successful hemostasis, respectively. In addition, missed patients achieved complete hemostasis with additional transcatheter arterial embolization and balloon compression, respectively. No complications were observed, including perforation, pancreatitis, and clipping bile duct and pancreatic duct by mistake.Conclusions Hemostasis with SureClip is safe, effective, and not expensive for post-EST bleeding. It could be the first choice for hemostasis in patients with post-EST bleeding refractory to balloon compression.
Keywords: Pancreatobiliary (ERCP/PTCD); Stones; ERC topics; Strictures